Nurse-Led Self-Management Support After Organ Transplantation – A Multicenter, Stepped-Wedge Randomized Controlled Trial - Regina van Zanten; Monique van Dijk; Joost van Rosmalen; Joost van Rosmalen; Denise K. Beck; AnneLoes van Staa; Ann Van Hecke; Ann Van Hecke; Emma K. Massey (Transplant International)
In this unblinded multi-center stepped-wedge randomized controlled trial the effectiveness of the nurse-led ZENN-intervention was tested in promoting self-management skills in comparison to standard care among heart, lung and kidney transplant recipients. This intervention is based on behaviour change theories and was conducted in four sessions over 6 months at the outpatient clinic. The experimental group received standard care, plus the ZENN-intervention, while the control group received only standard care. Both groups completed questionnaires at baseline, at 6 months and 1 year follow-up. At baseline, the experimental group (n = 69) scored significantly lower than the control group (n = 106) on the primary outcome Skills and Technique Acquisition (STA). No significant between-group differences were found on the secondary outcomes self-management, self-regulation, quality of life and medication adherence at T1 and T2. There was a significant increase on the self-management scale STA between T0 and T1 in the experimental group. Therefore, participants included in the experimental group had lower self-management skills at baseline and reported significant improvement after completing the intervention. No significant intervention effect was found in the primary analysis, however, for recipients with reduced self-management skills the intervention may be beneficial.Clinical Trial Registrationhttps://onderzoekmetmensen.nl/en/trial/24150, Netherlands Trial Register NL8469.